New constitutional law of Kenya : principles, government and human rights - Mbondenyi, Morris Kiwinda; Ambani, J. Osogo (LawAfrica, 2012)
The golden thread that cuts across the various chapters of the book is the emphasis that good constitutions anchor certain tenets that have garnered recognition as hallmarks of democratic dispensation. These hallmarks include the concept of separation of powers; the doctrine of the rule of law; constitutionalism and human rights. These attributes have largely been secured by the 2010 Constitution. Thus, this book is expected to contribute to this new promise by making knowledge on the Constitution accessible through breaking down and contextualising its provisions. It is certain to be useful t.